Shahbaz Bhatti : Martyr of the Suffering Church - Allen, John L., Jr., 1965- (Book collections on Project MUSE., 2017)
"When Shahbaz Bhatti, the lone Christian in Pakistan's cabinet and a determined campaigner for the rights of Christians and members of other faiths was killed, his Taliban-affiliated assassins probably hoped it would be the end of his influence. Instead, Bhatti's stature has only grown after death, and today he looms as a martyr and patron saint for persecuted Christians everywhere. His riveting life, from devoted altar boy in an overwhelming Muslim nation to human rights campaigner, from politician and government minister to martyr, is one of the great Christian dramas of our time, and as long as Christians are at risk anywhere in the world, Shahbaz Bhatti will be a source of inspiration and hope."--Publisher description.